Father Christmas needs a wee ! - Allan Nicholas (Red Fox, 2009)
A funny festive counting book in brilliantly bouncy rhyme! At every house Father Christmas eats and drinks the tasty treats have been left for him. But when he reaches number ten he realizes that he's forgotten to do something rather important AND he really, really, really, really needs a wee. Will Fatheer Christmas manage to fix his mistake in time and avoid wetting his Santa suit ? Find out in Nicholas Allan's fabulous new book.
Keywords: Père Noël; Noël; Littérature anglaise pour la jeunesse; Livres à compter; Livres illustrés pour enfants